Art literature for children and youth as the institute of socialization (using the example of V. Gapeev’s novel «Witch Fishery») - Aleinik, Lada V. (Journal of the Belarusian State University. Philology, 2020)
The history of the theory of personality socialization, its latest scientific interpretations is examined, the interdisciplinary demand is substantiated. The sociocultural and analytical potential of literature and literary criticism is reflected in the mapping and analysis of the social adaptation of the individual, the qualities of literary works as effective factors of socialization are investigated. The novel of the modern Belarusian writer V. Gapeev «Witch Fishery», addressed to an audience of young readers, reveals the mechanisms of socialization in it. Numerous causal relationships are traced to the social interaction of an individual with his immediate environment and society as a whole. It is emphasized that socialization contributes to the improvement of personality, helps not only to assimilate social experience, but also to transfer it. The role of fiction as one of the fundamental institutions of socialization is determined.